Financial inclusion, growth and poverty: Evidence from Africa in COVID-19 era - (:unkn) unknown (My University, 2023)
The Covid-19 pandemic threatens to undermine committed efforts to reduce poverty in Africa. Using panel data on 39 African countries covering the period 2004-2021, our analysis shows that financial inclusion, particularly access to financial services, can be an important driver of poverty reduction in African countries. in the era of Covid-19. Moreover, we have identified the reduction of inequalities as the main channel through which financial inclusion can contribute to alleviating poverty. These results are robust and consistent using different estimation methods and poverty change index. Faced with the risks of increasing extreme poverty due to Covid-19, a policy aimed at improving financial inclusion seems necessary.
Keywords: African Research